Significance of Conic Section in Daily Life and Real Life Questions Related to it in Different Sectors - Das, Prem Kumar; Sahani, Suresh Kumar; Mahto, Shyam Kishore (Jurnal Pendidikan Matematika, 2024)
Students tend to think of mathematics as, “that difficult, boring subject” that only exists within the walls of a classroom. Many students do not realize that mathematics is all around us occurring in our daily lives. Mathematics can be found easily in everyday activities such as cooking, driving, and even walking. Here, we are going to overview the conic section: ellipse, circle, parabola, hyperbola from different angle of life. In this report we will be analyzing a very crucial applications of conic section in the medical field, engineering field, some real life based questions will be sloved, some galleries specially a whispering gallery and some elliptical art works. We will be looking that how a conic section had given a great way to our life.